Influence of maternal-offspring behaviour on the growth of guzerá calves - Gabriele Voltareli da Silva; Bianca Vilela Pires; Sergio Pereira Lima; Luara Afonso de Freitas; Lenira El Faro; Maria Lucia Pereira Lima; Claudia Cristina Paro Paz (Boletim de Indústria Animal, 2017)
The present studyâ€™s objective was to verify the influence of behavioral characteristics such as strength at birth and human assistance on growth of GuzerÃ¡ breed calves until weaning, in addition to estimating the growth curve based on age, strength and need for human assistance of GuzerÃ¡ animals. A total of 73 calves were used, 39 males and 34 females. The calves were classified according to the strength at birth (presence (1) or absence (0) and the need for human assistance (HA = 1 received assistance and HA = 0 received no assistance) 4 hours after calving occurred. The calves were weighed at birth (WB), at 120 Â± 20 days (WA120) and during weaning at 210 Â± 20 days (WW). The animals were divided into 5 weight classes according to the ages and weights measured. The models of Brody, Von Bertalanffy, Richards, LogÃstico and Gompertz were tested to estimate animalsâ€™ growth until weaning. The birth month of the calves, sex and the need of human assistance influenced (P<0.05) WB and WA120. WW was influenced (P <0.05) by the effects of sex and the need for human assistance. Male calves had kept higher weights than females throughout the study. Among the models tested for growth curve estimation, the Von Bertalanffy model had the best fit for strength at birth and for human assistance. Asymptotic weight and maturity rate were higher in calves that did not require human assistance. The growth curve showed that the absence or presence of strength at birth does not affect weaning weight, while the need for human assistance impairs animal development until weaning.